2012
DOI: 10.1093/jrr/rrs102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bevacizumab treatment on p-boronophenylalanine distribution in murine tumor

Abstract: Previous studies have demonstrated that angiogenesis inhibitors can enhance tumor inhibitory effects of chemo- and radiotherapy via their action on tumor vessels. Here, we studied the effect of the angiogenesis inhibitor, bevacizumab (Avastin), on boron distribution in a murine tumor model. The human head and neck squamous cell carcinoma cell line was used for inoculation into mice. Boron-10 concentrations in tissues were measured by prompt γ-ray spectrometry (PGA). Hoechst 33342 perfusion and p-boronophenylal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In previous animal studies, BPA has been intraperitoneally administered due to the ease of the experimental procedure. [23][24][25][26][27] However, the pattern of increase in the blood remains unknown, and it is difficult to control blood concentration by intraperitoneal injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous animal studies, BPA has been intraperitoneally administered due to the ease of the experimental procedure. [23][24][25][26][27] However, the pattern of increase in the blood remains unknown, and it is difficult to control blood concentration by intraperitoneal injection.…”
Section: Discussionmentioning
confidence: 99%
“…In our PET analysis, CIV of 18 F‐FBPA also showed a continuous increase of uptake in the heart, suggesting an increase in the blood concentration of 18 F‐FBPA. In previous animal studies, BPA has been intraperitoneally administered due to the ease of the experimental procedure . However, the pattern of increase in the blood remains unknown, and it is difficult to control blood concentration by intraperitoneal injection.…”
Section: Discussionmentioning
confidence: 99%
“…Results are discordant in terms of drug delivery to the tumor: some studies show increased uptake after antiangiogenic therapy [ 20 , 34 , 67 71 ], but others report reduced drug delivery [ 72 77 ]. Enhanced tumor uptake of chemotherapeutics was concomitant in some instances with improvement of vessel functionality [ 68 , 78 ], whereas in other cases there was worsening of perfusion/permeability [ 34 , 69 ]. Inefficient drug delivery was often associated with the reduction of tumor perfusion or vessel permeability.…”
Section: Effects Of Antiangiogenics On Pharmacokinetics and Tumor Uptmentioning
confidence: 99%
“…Some studies clearly illustrate the importance of the treatment schedule, showing the temporary time window in which the antiangiogenic agent exerts beneficial effects on drug pharmacokinetics. In fact, drug penetration in tumors was enhanced only when the chemotherapeutic agent was administered within a narrow interval after anti-VEGF therapy (i.e., bevacizumab) [ 20 , 67 , 68 ].…”
Section: Effects Of Antiangiogenics On Pharmacokinetics and Tumor Uptmentioning
confidence: 99%
“…In combination with chemotherapy anti-VEGF improves anti-cancer therapy, although the outcome depends on the cancer type and on the scheduling of the treatment [ 2 ]. The scheduling issue arises from the fact that anti-VEGF decreases perfusion of chemotoxic agents in some cancers, including melanoma [ 3 ], breast cancer [ 4 , 5 ] and ovarian cancer [ 6 ], while it increases perfusion of chemotoxic agents in other cancers, such as colon cancer [ 7 , 8 ] and head and neck cancer [ 9 ]. More recently Asrid et al [ 10 ] reported a rapid decrease in the delivery of chemotherapy to the tumor in patients of non-small cell lung cancer (NSCLC) after anti-VEGF therapy, highlighting the importance of drug scheduling in combination therapy when anti-VEGF is one of the drugs.…”
Section: Introductionmentioning
confidence: 99%